Discovery of 2, 6–difluorobenzyl ether series of phenyl ((R)–3–phenylpyrrolidin–3–yl)sulfones as surprisingly potent, selective and orally bioavailable RORγt inverse agonists. Issue 19 (1st October 2020) - Duan, James J.-W.; Jiang, Bin; Lu, Zhonghui; Stachura, Sylwia; Weigelt, Carolyn A.; Sack, John S.; Khan, Javed; Ruzanov, Max; Wu, Dauh–Rurng; Yarde, Melissa; Shen, Ding–Ren; Zhao, Qihong; et al.
Graphical abstract: Abstract: In an effort to discover oral inverse agonists of RORγ t to treat inflammatory diseases, a new 2, 6–difluorobenzyl ether series of cyclopentyl sulfones were found to be surprisingly more potent than the corresponding alcohol derivatives. When combined with a more optimized phenyl (( R )–3–phenylpyrrolidin–3–yl)sulfone template, the 2, 6–difluorobenzyl ethers yielded a set of very potent RORγ t inverse agonists (e.g., compound 26, RORγ t Gal4 EC50 11 nM) that are highly selective against PXR, LXRα and LXRβ. After optimizing for stability in human and mouse liver microsomes, compounds 29 and 38 were evaluated in vivo and found to have good oral bioavailability (56% and 101%, respectively) in mice. X–ray co–crystal structure of compound 27 in RORγ t revealed that the bulky benzyl ether group causes helix 11 of the protein to partially uncoil to create a new, enlarged binding site, which nicely accommodates the benzyl ether moiety, leading to net potency gain.